2021
DOI: 10.36909/jer.v9i2.9395
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of discharge coefficient and energy dissipation of flow over a stepped morning glory spillway

Abstract: A morning glory spillway usually has an ogee shaped crest and conveys spill water flow to its downstream vertical shaft followed by a horizontal tunnel. The ungated morning glory spillways should convey variable discharges, which nonlinearly depends on the reservoir water elevation. The variation of discharge for unit length of the crest may cause challenges on design of downstream crest curve (which affects coefficient of discharge and downstream crest negative pressure). Furthermore, formation of a horizonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Alkhamis et al, in 2021 [36], also used CFD numerical evaluation to predict the discharge coefficients over an ogee-shaped crest. In the same year, Haktanir and Khalaf [37] analyzed the discharge coefficients for radial-gated ogee spillways and concluded that the results in [4] are not sufficient to accurately estimate the discharge over an ogee spillway for the case of partially open gates.…”
Section: 𝑄 = 𝐶𝐿𝐻 /mentioning
confidence: 99%
“…Alkhamis et al, in 2021 [36], also used CFD numerical evaluation to predict the discharge coefficients over an ogee-shaped crest. In the same year, Haktanir and Khalaf [37] analyzed the discharge coefficients for radial-gated ogee spillways and concluded that the results in [4] are not sufficient to accurately estimate the discharge over an ogee spillway for the case of partially open gates.…”
Section: 𝑄 = 𝐶𝐿𝐻 /mentioning
confidence: 99%
“…The use of the Computational Fluid Dynamics (CFD) methods increases after the development of computer technology. Many researchers have analyzed the effect of different step geometries on energy dissipation rates numerically (Arjenaki et al, 2020;Ashoor and Riazi, 2019;Ghaderi et al, 2021Ghaderi et al, , 2020Hekmatzadeh et al, 2018;Li et al, 2020Li et al, , 2018Mohammad et al, 2016;Reeve et al, 2019;Shahheydari et al, 2015;Tabbara et al, 2005;Alkhamis et al 2021). In this study, trapezoidal stepped spillways (TSS), which have not been studied in the literature, were analyzed numerically with Flow3D software.…”
Section: Introductionmentioning
confidence: 99%